Peran Ekuitas Merek dalam Memediasi Pengaruh Aktivitas Pemasaran Media Sosial terhadap Keputusan Memilih Sekolah - Dodhy Hyronimus Ama Longgy; Okto Irianto; Henie Poerwandar Asmaningrum; Tini Adiatma; Tarsisius Kana (CV. Muris Global Education, 2026)
This study examines the effect of Social Media Marketing Activities on Purchase Decision through Brand Equity in the context of Catholic educational institutions under Yayasan Pendidikan dan Persekolahan Katolik Merauke. A quantitative explanatory approach was applied by involving 100 parents whose children study at YPPK schools. Data were collected using a structured questionnaire with a five-point Likert scale. Social Media Marketing Activities were measured through social media understanding, entertainment, interaction, trendiness, customization, and word of mouth. Brand Equity was measured through brand awareness, brand association, brand loyalty, and perceived quality, while Purchase Decision was measured through school choice decision, confidence in school choice, and willingness to recommend the school. The findings show that Social Media Marketing Activities have a significant effect on Purchase Decision, although the direct relationship is negative. Social Media Marketing Activities have a positive and significant effect on Brand Equity, and Brand Equity has a positive and significant effect on Purchase Decision. Furthermore, Brand Equity partially mediates the relationship between Social Media Marketing Activities and Purchase Decision. This study contributes to educational marketing literature by positioning Brand Equity as a key mechanism that explains how social media activities influence parents’ school choice decisions. The study offers originality by examining digital marketing, brand equity, and school choice decisions in Catholic educational institutions, a context rarely examined in previous social media marketing studies. YPPK should manage social media not merely as promotional media, but as a strategic instrument to strengthen reputation, trust, perceived quality, and institutional values.